Cover Picture: Inherently Chiral Spider‐Like Oligothiophenes (Chem. Eur. J. 31/2016). Issue 31 (3rd June 2016) - Sannicolò, Francesco; Mussini, Patrizia R.; Benincori, Tiziana; Martinazzo, Rocco; Arnaboldi, Serena; Appoloni, Giulio; Panigati, Monica; Quartapelle Procopio, Elsa; Marino, Valentina; Cirilli, Roberto; Casolo, Simone; Kutner, Wlodzimierz; et al.
Abstract : The racemate of an inherently chiral "spider‐like" octathiophene monomerT83, in which chirality is generated by torsion in its backbone, was synthesized. In the cover image, the ( S )‐T83 has woven a highly selective chiral web in which enantiomorphic insects (l ‐ andd ‐DOPA, R ‐ and S ‐FcA) are differently entrapped. More information can be found in the Full Paper by P. R. Mussini, T. Benincori, R. Martinazzo et al.on page 10839 .